The Role of Influencers in the Digital Era as an Effort to Promote Indonesian Tourism Destinations - Kharisma Citra; Jonathan Napitupulu; Rino Febrianno Boer (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2025)
In the rapidly evolving digital era, the Indonesian tourism sector faces challenges in reaching and engaging millennial and Gen Z travelers through traditional promotion methods. Despite the widespread use of influencers in tourism marketing, there is limited understanding of how influencer credibility, platform characteristics, and narrative styles specifically impact tourist decision-making in Indonesia. This study aims to fill this gap by analyzing the role of social media influencers in shaping perceptions and influencing travel choices toward Indonesian destinations. Employing a qualitative approach that includes in-depth interviews, social media content analysis, and observation of digital trends, the research seeks to interpret how participants construct meaning through their engagement with influencer content. The findings offer rich, contextual insights for tourism stakeholders to optimize influencer collaborations and tailor marketing strategies to better resonate with target audiences in the digital landscape.